Model Penerimaan Aplikasi Elektronik Laporan Harta Kekayaan Penyelenggara Negara (E-LHKPN) Pada Pejabat Aparatur Sipil Negera di Lingkungan Universitas Cenderawasih - Simanungkalit, Lisnawati; Asnawi, Meinarni; WIjaya, Anthonius H.C (Jurnal Akuntansi, Audit, dan Aset, 2021)
The purpose of this study aims to determine the acceptance model of the State Administration ofWealth Report (E-LHKPN) application to state civil servants in the Cenderawasih Universityenvironment. The model used to explain the acceptance of the E-LHKPN system is the TechnologyAcceptance Model (TAM) with four latent variables.The type of data used in this research is quantitative data obtained from online questionnairesusing google Forms. The type of sampling used is non-probability sampling technique/census, wherethe sample is distributed to all officials who are required to report in the Cenderawasih UniversityEnvironment. The number of samples as many as 127 must report, calculated using the StructuralEquation Modeling (SEM) analysis technique which is one of the analysis techniques using the PartialLeast Square (PLS) 7.0 analysis tool program, using the warpPLS software.Based on the data analysis, the results obtained are as follows: perceived ease of use has asignificant effect on perceived benefits of use, perceived ease of use has a significant effect onbehavioral attitudes, perceived benefits of use have a significant effect on behavioral attitudes,perceptions of ease of use have an indirect effect on behavioral attitudes mediated by benefits.